O Jerzym Mierzejewskim - HENDRYKOWSKI, MAREK (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
About Jerzy Mierzejewski For many years the excellent painter-formist Jerzy Mierzejewski (1917-2012) was the eminent figure of artistic life in postwar Poland. He was also an academic, a professor at the famous Film School in Łódź. The article presents the significance of Mierzejewski in paving the path for Polish cinematographic art and for the international successes of many Polish filmmakers (i.e. Andrzej Wajda, Roman Polański, Adam Holender, Krzysztof Zanussi, Krzysztof Kieślowski, Zbigniew Rybczyński and many others).